Can digital climate services help avert agricultural losses and damage? Insights from a social experiment with women farmers in Bangladesh - Amjath Babu, Tharayil Shereef; Sumona Shahrin; Saleh Mohammad Shahriar; Mustafa Kamrul Hasan; Krupnik, Timothy J. (TAFSSA, 2023)
This research note explains the results of social experiment designed with three primary objectives. These include (1) to mitigate the digital divide concerning the accessibility of forecasted weather information and crop advisories for women farmers in Bangladesh and (2) to assess the potential impact of a digital climate advisory tool on the agricultural practices of women farmers. Finally, (3) we sought to assess the potential advantages of climate-smart agriculture facilitated by digital advisory tools for stakeholders in the value chain, such as microfinance institutions offering crop loans in areas facing higher weather-related risks. ‘Agvisely’ is a farming systems decision support system (DSS) for Bangladesh. It serves as the digital climate advisory tool used in this experiment. The study involved 120 female farmers in Patuakhali district of coastal Bangladesh. We aimed to assess the impact of climate services on the cultivation of mung bean (Vigna radiata) and boro rice (Oryza sativa) during the winter rabi season.